علاج التهاب الإحليل السيلاني الحاد عند الذكور - حرفوش, أيمن (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة خمسةً وسبعين مريضاً مصاباً بالتهاب الإحليل السيلاني الحاد، والذين راجعوا مشفى الأسد الجامعي في اللاذقية في الفترة الواقعة بين عامي 2007-2005, حيث تم عزل المكورات البنية عند جميع المرضى. قسم المرضى إلى ثلاث مجموعات، تضم كل مجموعة 25 مريضاً حيث أعطيت المجموعة الأولى عقار Pefloxacin 400/mg في اليوم الأول: 800/mg دفعة واحدة مساءً وبعدها400/mg كل 12ساعة لمدة أربعة أيام حيث حصل المرضى على 4000 /mg. المجموعة الثانية عولجت على الشكل الآتي: تم إعطاء المرضى حقنتين عضليتين بفاصل زمني 48 ساعة من عقار Spectinomycin hydrochloride 2/g. مجموع ما حصل عليه المرضى 4/g. المجموعة الثالثة: عولجت على الشكل الآتي: في البداية تم إعطاء المرضى حقنتين عضليتين بفاصل زمني 48 ساعة من عقار Spectinomycin hydrochloride 2/g، وبعدها تم إعطاء المرضى عقار Pefloxacin 400/mg بمعدل 400/mg كل 12 ساعة لمدة خمسة أيام حيث حصل المرضى على 4000/mg. إن أفضل النتائج تم الحصول عليها في المجموعة الثالثة حيث حصلنا على الشفاء التام عند جميع المرضى. The study covered seventy five patients of acute gonococal urethritis. These patients have visited Al Assad University Hospital of Lattakia in 2005-2007. The gonococci were isolated in all patients. The patients were divided into three groups. Each group consisted of 25 patients. The first group was given Pefloxacin 400/mg. On the first day, they were given 800 mg in the evening and 400 mg every 12 hours for four days. So the patients took 4000 mg. The second group was treated by giving the patients two muscle injections of Spectinomycin hydrochloride 2/g. The period between the two injections was 48 hours. The third group was treated as follows: first, the patients were given two muscle injections of Spectinomycin hydrochloride 2/g. The period between the two injections was 48 hours. Then, the patients were given Pefloxacin 400/mg every 12 hours for five days. So the patients took 4000mg. The best results were obtained with the third group where all the patients completely recovered.